La cultura tributaria en los comerciantes del mercado central de la ciudad de Iquitos, periodo 2021 - García Flores, Ana Paulina (2022)
The tax culture represents the knowledge that individuals possess in matters of a tax nature, which leads to generating a healthy conscience in the voluntary compliance with tax obligations, as well as contributing to reducing tax evasion in order to increase tax levels collection for the benefit of the state. The present investigation called “The Tax Culture in the merchants of the Central Market of the city of Iquitos, period 2021”, presented as a general objective to determine the level of the tax culture that the merchants of the central market of the city of Iquitos present in the period 2021. Likewise, the research was of a quantitative type and of a descriptive non-experimental-cross-sectional design. From the analysis and discussion of the result obtained, it was possible to determine that the merchants of the aforementioned market have a low level of tax culture.